Dysfunction of Collaborative Governance in the Handling Policy of Covid-19 at Jambi Province - Muhammad Ichsan Kabullah; Sudarmoko; Hendri Koeswara; Fajri Rahman; Azwar (Direktorat Riset dan Pengabdian kepada Masyarakat, 2021)
Current research on public administration has generally concluded thatcollaborative governance is a critical factor in solving thecontemporary crisis. Collaborative governance has been suggested asa mechanism that brings state and private stakeholders together inpolicymaking. Through a case study in the Jambi Province, we find thatthe collaboration between local governments and society has beeneffective to solve the crisis because they may share understanding toprioritise the Covid-19 pandemic as a common problem. At the sametime, the religious tension also had a positive impact on thecollaboration. However, the collaboration performance has followedseveral challenges such as incompatible procedures, inequality for thesame access between individuals, and intervention by local elites.